Case report: A case report and literature review on spontaneous bacterial peritonitis induced by intestinal barrier damage in a colorectal cancer patient with malnutrition - Xu, Peng; Shi, Sanbao; Yu, Zhiyu; Li, Da; Zhang, Cheng (Frontiers in Oncology, 2025)
BackgroundSpontaneous bacterial peritonitis (SBP) is an infectious condition characterizing the presence of bacterial infection in the peritoneal fluid with no apparent source of infection within the abdomen. It is extremely rare for patients with malnutrition after colorectal cancer (CRC) surgery to develop SBP. This is the first ever case reported case of SBP resulting from intestinal barrier compromise in a patient with colorectal cancer with malnutrition.Case summaryA 72-year-old woman with malnutrition was diagnosed with CRC, and following brief nutritional support, she underwent the laparoscopic-assisted radical right hemicolectomy. The patient was then diagnosed with peritonitis after the operation. An emergency laparotomy was performed, and the patient was finally diagnosed with SBP. The patient ultimately recovered following a series of appropriate postoperative supportive treatments.ConclusionThis case highlights the poor outcomes of short preoperative nutritional therapy in CRC patients with malnutrition. Further studies should investigate the role of the intestinal barrier function in the recovery of patients with CRC after surgery.